Metabolic Profile of Patients with Recurrent Nephrolithiasis: A Hospital Based Cross-Sectional Study from a Tertiary Care Centre in Nepal - Krishna Kumar Sah; Rajani Hada; Anil Baral (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Nephrolithiasis is a recurrent condition with multifactorial metabolic causes that vary across populations. Identifying metabolic abnormalities among recurrent multiple stone formers is essential for targeted prevention. This study aimed to evaluate the spectrum and frequency of metabolic derangements among patients with recurrent nephrolithiasis including both recurrent single- and multiple-stone formers presenting to a tertiary care center in Nepal. Material and Methods: This hospital based cross-sectional observational study was conducted in the Department of Nephrology, Bir Hospital, from February 2018 to January 2019. Adult patients (≥18 years) with a history of recurrent or multiple renal stones confirmed by ultrasonography were included. Demographic and clinical data were recorded, and 24-hour urine samples were analyzed for calcium, citrate, oxalate, uric acid, and volume. Serum calcium, phosphate, uric acid, and creatinine were measured. Metabolic abnormalities were defined using standard thresholds, and data were analyzed using descriptive statistics, the Chi-square test, and logistic regression with R version 4.4.1. A p-value <0.05 was considered statistically significant. Results: A total of 120 patients with recurrent nephrolithiasis were evaluated. Based on ultrasonographic findings at presentation 73 were recurrent multiple-stone formers and 47 were recurrent single-stone formers. Hypocitraturia (81%) and hyperoxaluria (70%) were the most prevalent abnormalities, followed by hypercalciuria (25%) and hyperuricosuria (8%). Multiple metabolic abnormalities were significantly more common among recurrent multiple stone formers (71% vs. 57%, p = 0.009). Serum biochemical parameters and renal function were comparable between groups. On multivariable logistic regression, hyperoxaluria showed a non-significant trend toward higher odds of multiple nephrolithiasis (aOR = 1.99; 95% CI: 0.88–4.58; p = 0.10). Conclusion: Patients with recurrent or multiple nephrolithiasis in our population exhibit a high burden of metabolic abnormalities, particularly hypocitraturia and hyperoxaluria. Comprehensive metabolic evaluation and tailored interventions such as alkali therapy, adequate hydration, and dietary counselling are essential to reduce recurrence and long-term disease burden.